Video Game-based Digital Learning in the Development of Vocabulary Knowledge - Sandi, Muhamad; Murtiningsih, Tenny; Riyanto, Sugeng; Ratih, Koesoemo; Kusparlina, Eny Pemilu (Universitas Muhammadiyah Surakarta, 2023)
The use of technology in learning is a necessity. One of the technologies that can be used in learning is video games because of their proximity to students. This study aims to describe the development of video game-based learning in learning English vocabulary. The approach used in this research is descriptive qualitative. The data in this study were collected by interview method. The findings resulting from this research are in the form of video games that are played by many students and can add to students' English vocabulary, namely video games in the form of online games such as Clash of Clans, RPG Toran online, and PC games in the form of FIFA 23. These games can help students improve vocabulary. English words through the hint language and the notifications that are in it. However, this method has a weakness in the form of unorganized vocabulary that students learn through video games and each student has a different level of vocabulary mastery according to the video game he likes.